Tocilizumab in Extracranial Giant-Cell Arteritis and Takayasu Arteritis: A Multicentric Observational Comparative Study - Carmen Lasa-Teja; Javier Loricera; Diana Prieto-Peña; Fernando López-Gutiérrez; Pilar Bernabéu; María Mercedes Freire-González; Beatriz González-Alvarez; Roser Solans-Laqué; Mauricio Mínguez; Iván Ferraz-Amaro; Santos Castañeda; Ricardo Blanco; et al. (Sci)
Tocilizumab (TCZ) has demonstrated potential efficacy in managing large-vessel (LV) vasculitis such as giant-cell arteritis (GCA) and Takayasu arteritis (TAK). Despite the shared characteristics between the LV-GCA phenotype and TAK, there are differences between both entities that may affect therapeutic responses to TCZ. We aim to assess and compare the effectiveness and safety of TCZ in patients with LV-GCA and TAK. Multicenter, observational study on 70 LV-GCA patients and 57 TAK patients treated with TCZ. Outcomes were assessed at baseline and at 1, 3, 6 and 12 months post-treatment initiation. The variables analyzed included the following: (a) the achievement of clinical remission and improvement in laboratory markers; (b) imaging-based disease activity; (c) a glucocorticoid (GC)-sparing effect; and (d) side events and a safety profile. At the treatment initiation, TAK patients were younger, exhibited longer disease duration, had received more prior biologics, and were on higher doses of prednisone compared to LV-GCA patients. While TAK patients showed a slower initial clinical response, remission rates at 12 months were comparable between groups (74.5% for LV-GCA vs. 76.9% for TAK). Both groups experienced rapid laboratory marker improvement and a significant GC-sparing effect. However, complete imaging resolution was observed in only 18.9% of LV-GCA patients and 21.1% of TAK patients. The safety profile was similar in both groups, with severe infections leading to TCZ discontinuation in four LV-GCA and three TAK patients. In clinical practice, TCZ demonstrates similar efficacy in promoting remission and reducing GC dependency in both LV-GCA and TAK patients. Nonetheless, discrepancies between clinical outcomes and imaging improvement highlight the need for further investigation into disease monitoring and management strategies.